Study of organic acids in almond leaves - Lenchyk, L; Samaneh, Bayat; Kyslychenko, V (Annals of Mechnikov’s Institute, 2020)
Introduction. Almond (Amygdalus communis) is a stone fruit, from the Rosaceae family, closest to the peach. It is spread throughout the entire Mediterranean region and afterwards to the Southwestern USA, Northern Africa, Turkey, Iran, Australia and South Africa. It is sensitive to wet conditions, and therefore is not grown in wet climates. Iran is located in the semi-arid region of the world. Because of its special tolerance to water stress, almond is one of the main agricultural products in rainfed condition in Iran. Almond leaves have been investigated for their phenolic content and antioxidant activity. It was found that total antioxidant activity and phenolic compounds exhibited variations according to season, plant organ (leaf and stem) and variety. Analysis of previous research on almonds focused on investigating compounds mostly in seeds and phenolic compounds in leaves, but organic acids in leaves have not been studied. Aim of this study was investigation of organic acids in leaves of almond variety which is distributed in Razavi Khorasan province of Iran. Materials and Methods. In August 2012 almond leaves were collected in Iran, dried and grinded. The study of qualitative composition and quantitative determination of carboxylic acids in almond leaves was carried out by gas chromatography with mass spectrometric detection. For determination organic acids content, to 50 mg of dried plant material in 2 ml vial internal standard (50 μg of tridecane in hexane) was added and filled up with 1.0 ml of methylating agent (14 % BCl3 in methanol, Supelco 3-3033). The mixture was kept in a sealed vial during 8 hours at 65 °C. At this time fatty oil was fully extracted, and hydrolyzed into its constituent fatty acids and their methylation was done. At the same time free organic and phenolcarbonic acids were methylated too. The reaction mixture was poured from the plant material sediment and was diluted with 1 ml of distilled water. To extract methyl esters of fatty acids 0.2 ml dichloromethane was filled up, gently shaken several times within an hour and then obtained methyl esters extract was chromatographed. Injection of sample (2 μl) in a chromatographic column was carried out splitless, which allowed introducing the sample without flow division and significantly (10-20 time) increased sensitivity to chromatography analysis. Content of organic acids were determined on Agilent Technologies 6890 chromatograph with mass spectrometric detector 5973; chromatography column - INNOWAX, capillary diam. 0.25 mm and a length of 30m; the rate of carrier gas (helium): 1.2 ml/min; heater temperature - 250°C; thermostat temperature was programmed from 50 to 250 °C with a speed of 4 °C / min. For components identification, library of mass spectra NIST05 and WILEY 2007 with a total number of spectra more than 470,000 in conjunction with AMDIS and NIST programs were used. The statistical processing of results was carried out using package Statistica 6.0. The error does not exceed 5%. Results and discussion. 32 organic acids were established in almond leaves and their quantitative values were determined, using internal standard method. Overall, plant raw material contained 1.80% of the organic acids, including (%) – 0.75 fatty; 0.95 di- and three carboxylic; 0.10 phenol carboxylic acids. Among the carboxylic acids, oxalic and malic acid were the largest with- 3616.41 (38.23%) and 3343.03 (35.34%) mg / kg, respectively. Palmitic and linoleic acids dominated among the fatty acids, their content was determined as (mg/kg) 2343.49 and 1963.60 that were 30.98 % and 25.96% respectively of the total fatty acids. Among phenol carboxylic acids, the largest content was defined for benzoic acid. It was 488.43 mg / kg or 50.16% of the total amount of phenol carboxylic acids. Conclusion. Almond leaves were investigated by gas chromatography. 32 organic acids were established and their quantitative value were determined. It was found that almond leaves contain 1.80% of the organic acids, including (%) – 0.75 fatty acids; 0.95 di- and three carboxylic acids; 0.10 phenol carboxylic acids. The results of this study are significant for determining beneficial compounds in almond leaves, so making use of these plant raw material as source of new medicines in the future is possible.